(untitled) (Sirte University Journal of Humanities, 2023)
The research deals with the philosophy of civilization as Whitehead puts it, by extracting it from what was mentioned in his book The Adventure of Ideas and its comparison with some other philosophies. From a philosophical point of view, it tends to the vital trend that sees the entire existence of a living nature, in addition to the contemporary physical theories that say the transformation of matter, which gives it some vitality. This is evident from his use of the word mind instead of the mind or the soul. He believes that peace expresses civilizational stability, as the harmony between truth and beauty is achieved by which the congruence between essence and appearance is achieved, which achieves relative perfection. Stability does not last, because perfection has not been achieved in a way that satisfies the soul, which leads it to embark on a new adventure, and continues on that until it completes its cycle and perishes. Keywords: (civilization, dialectical approach, ideas, adventure.